Slovak Republic : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency Module for the Slovak Republic. Fiscal management and transparency in the Slovak Republic have improved substantially over the last two years, and the country now meets the fiscal transparency code's standards in several areas. Key weaknesses in the coverage of fiscal operations and in budget preparation have been largely addressed: budget preparation is now cast within clearly identified medium-term macroeconomic framework and constraints; and budget execution and reporting have new financial control and internal audit procedures.